The Effect of Adolescent Therapeutic Group Therapy (TKT) on the Development of Adolescent of Islamic Boarding School in Tasikmalaya - Ridwan Kustiawan; Iwan Somantri (Universitas Muhammadiyah Surakarta, 2022)
The stage of adolescent development is a unique stage of development, adolescents must face changes both physically, cognitively, and emotionally that can cause stress and trigger a unique behaviour in adolescents. Today's Muslim youth are many who follow the Islamic boarding school program. This causes the development of adolescents that are less than optimal, if they cannot adapt to the life of the Islamic boarding school, so that it can interfere with the learning process in the Islamic boarding school. And furthermore, their mental health will be disturbed in their adolescent development, such as being less independent, unable to make decisions and having difficulty interacting with peers. One of the efforts to deal with developmental problems faced by adolescents is the therapeutic group therapy (TKT) approach. The purpose of this study was to determine the effect of therapeutic group therapy on the ability of adolescents to stimulate identity development in high school students at the Ibadurrahman Islamic Boarding School, Tasikmalaya City. The design used is